The Recovery of EU: Taking Stock and the Way Forward - Beev, Ivailo; Todorov, Ivan (Research Papers, 2021)
This paper emphasizes the underlying economic implications of the proclamation plan for a "Next generation EU" with a central focus on the Proposal for a Regulation on the Recovery and Resilience Facility. The implementation of this plan is necessary, but not a sufficient condition for a successful return of EU economies to the trajectory of GDP before the crisis - in the short term additional and targeted fiscal impulse is needed, while in the long run the EU inevitably needs to reformulate its fiscal management in the direction of adapting fiscal rules to the new reality and even conducting a common fiscal policy.
Keywords: Reforms; Economic crises; COVID-19; Public investment; Next generation EU